Survey of the Properties of Waxed Duplex Cartons Used in Frozen Shrimp Industry - GOPAL, T. K SRINIVASA; GOVINDAN, T K (Fishery Technology, 2017)
Waxed duplex cartons collected from different prawn freezing factories were evaluated for their physico-chemical properties such as bursting strength, puncture resistance, water proofness, tearing, strength, tensile strength, elongation, moisture content, thickness, weight of the carton, dimension, wax content and saponifiable matter. The results are discussed from the point of view of formulation of standards for this most widely employed packaging material for frozen :fishery products in the country.